UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 96% RIMPANG LENGKUAS MERAH (Alpinia purpurata (Vieill.) K.Schum) TERHADAP BAKTERI Staphylococcus aureus - Rakhmadhan Niah; Saftia Aryzki; Anna Khumaira Sari; Shela Puzi Dina (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Alpinia purpurata (Vieill.) K.Schum contains flavonoids, tannins, saponins, and terpenoids which have bacterial inhibitory power. This study aims to determine the antibacterial activity test of ethanol extract 96% Alpinia purpurata (Vieill.) K.Schum on the growth inhibition power of Staphylococcus aureus. This research is an experimental research. Antibacterial activity test of extract ethanol 96% Alpinia purpurata (Vieill.) K.Schum using Cup Plate Technique with concentrations of 40%, 30%, 20%, 10% and 5%, Clindamycin concentration 50Î¼g/ml as control (+) and 96% ethanol as control (-) in each treatment replication 4 times. The results diameter of the inhibitory zone formed was then analyzed by Statistical Producy Service Solution (SPSS) version 17. The results showed that extract ethanol 96% of Alpinia purpurata (Vieill.) K.Schum had inhibitory activity on the growth of Staphylococcus aureus. The average diameter of the extract ethanol 96% inhibition zone of Alpinia purpurata (Vieill.) K.Schum with a concentration of 40%, 30%, 20%, 10% and 5%, positive control (clindamycin), and negative control (96% ethanol) respectively on Staphylococcus aureus bacteria is 28.06 mm; 25.17 mm; 23.15 mm; 20.38 mm; 18.34 mm; 30.13 mm; 0 mm. There are significant differences in diameter of inhibitory zones between concentrations of extract ethanol 96% of Alpinia purpurata (Vieill.) K.Schum on the growth of Staphylococcus aureus bacteria with significance values 0,000.